Review article: recent advances in pharmacogenetics and pharmacokinetics for safe and effective thiopurine therapy in inflammatory bowel disease. Issue 8 (14th February 2016) - Moon, W.; Loftus, E. V.
Summary: Background: Azathioprine and mercaptopurine have a pivotal role in the treatment of inflammatory bowel disease (IBD). However, because of their complex metabolism and potential toxicities, optimal use of biomarkers to predict adverse effects and therapeutic response is paramount. Aim: To provide a comprehensive review focused on pharmacogenetics and pharmacokinetics for safe and effective thiopurine therapy in IBD. Methods: A literature search up to July 2015 was performed in PubMed using a combination of relevant MeSH terms. Results: Pre‐treatment thiopurine S‐methyltransferase typing plus measurement of 6‐tioguanine nucleotides and 6‐methylmercaptopurine ribonucleotides levels during treatment have emerged with key roles in facilitating safe and effective thiopurine therapy. Optimal use of these tools has been shown to reduce the risk of adverse effects by 3‐7%, and to improve efficacy by 15–30%. For the introduction of aldehyde oxidase (AOX) into clinical practice, the association between AOX activity and AZA dose requirements should be positively confirmed. Inosine triphosphatase assessment associated with adverse effects also shows promise. Nucleoside diphosphate‐linked moiety X‐type motif 15 variants have been shown to predict myelotoxicity on thiopurines in East Asian patients. However, the impact of assessments of xanthine oxidase, glutathione S‐transferase, hypoxanthine guanine phosphoribosyltransferase and inosine monophosphate dehydrogenase appears too low to favour incorporation into clinical practice. Conclusions: Measurement of thiopurine‐related enzymes and metabolites reduces the risk of adverse effects and improves efficacy, and should be considered part of standard management. However, this approach will not predict or avoid all adverse effects, and careful clinical and laboratory monitoring of patients receiving thiopurines remains essential.